Nanosilica functionalized to switch from dormant to active for gas migration mitigation in Portland cement. (3rd September 2021) - Boul, Peter J.; Shanmugam, Sivaprakash; Johnson, Kenneth D.
Abstract: We describe the development of a nanosilica‐based oil and gas well cement additive which reduces the risk of casing‐casing annulus (CCA) and sustained casing pressure (SCP) through gas migration mitigation. Nanosilicas added to oil and gas well cement have been shown to accelerate cement hydration and reduce the cement porosity and permeability. While these qualities can potentially reduce the risk of zonal isolation loss, there are known rheological effects associated with adding nanosilicas to cements. It is known that cements loaded with nanosilicas produce gels prematurely, which has the deleterious effect of leading to air entrainment in cement and can also effect the pumpability of the cement slurry. This property can also interfere with gas migration mitigation because it is the formation of the gel that reduces the hydrostatic pressure on the formation. This can, in‐turn, allow for fluid from the formation to invade the cement prior to building enough mechanical strength to resist the fluid influx. The nanosilica product described in this article has been developed to display no gelation effect in the cement and a rapid hydration onset. These performance attributes are due to a specialized functionalization or coating on the nanosilica particle. At temperatures equal to or below 120°F (49°C), this functionalization renders the nanosilica inert from the cement until its timed degradation and thus does not interact with the cement phases responsible for the gelation behaviour observed with other commercially available nanosilicas in the process of cement placement.